Inclusive sustainable landscape management in West and Central Africa: enabling co-designing contexts for systemic sensibility - Sobratee-Fajurally, N.; Mabhaudhi, Tafadzwanashe (CGIAR Initiative on West and Central African Food Systems Transformation, 2022)
The report creates contexts for a systemic understanding of the CGIAR Transforming agric-food system (TAFS-WCA) initiative starting with work package (WP) 3 and expanding the causality effects across the other WPs of the Initiative. The main focus of WP3 is inclusive landscape management, whereby access to and proper use of land and water resources is a prerequisite to building a healthy, productive environment for resilient agri-food systems and livelihoods. Mapping synergies with other Work Packages ensure that respective contributions are integrated and impactful. The process intends to provide policymakers, researchers, and practitioners with a strategic framework to activate solutions temporarily with a stakeholder-defined suite of scenarios.